Monitoring Data Perubahan Suhu, CO dan CO2 Secara Real Time Menggunakan MySQL - Randi Setiawan; Warsito Warsito; Junaidi Junaidi; Sri Wahyu Suciyati (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2020)
This research is related to making a system to display data on temperature changes, CO, and CO2 monitoring results in real time make use of MySQL. The measuring instrument used consisted of an MQ-7 sensor to detect CO gas, a MQ-135 sensor to detect CO2 gas, a DHT-22 sensor to measure the temperature and a microcontroller as a control system. Measurement data is displayed on the PC server using an interface created through the Visual Basic 2010 program and saved to the Mysql database. In this research, a baudrate of 19200 bps was used so that data transmission could be faster so that it supported realtime data transmission. Based on the research, it was found that the greater the boudrate value used, the faster time it takes to send data. In this study, a baudrate of 19200 bps was used so that data transmission could be faster so that it supported realtime data transmission. Based on the research, it was found that the greater the boltrate value used, the faster time it takes to send data. Based on the results of tests conducted, MySQL monitoring system is running well. The MySQL can display data on temperature changes, CO, and CO2 measurement data in the form of tables in real time.